INTERELASI HINDU DENGAN BUGIS: MENGGALI AJARAN SANATANA DHARMA DALAM KEPERCAYAAN TOLOTANG - Sugiarti Sugiarti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Tolotang or Towani Tolotang is a Hindu community found in South Sulawesi. This community is part of the Bugis ethnicity, but there are differences with Bugis in general, because it still maintains old beliefs. This belief is similar to the teachings influenced by Hinduism, which developed in the Indonesian archipelago, especially in the use of offerings in rituals. The mention of the Supreme Deity, Dewata Seuwae also bears a resemblance to the god Shiva in Hinduism, the terms Batara Guru, Sangiang or Sangeng Serri, pèrètiwi are deities contained in Hinduism. Although at the level of tradition, Tolotang is different from Bali and India, but in essence contains similarities. His recognition of being a Hindu is not solely to maintain the existence and recognition of the state, but also to use Hinduism as a